Camping - Gewinner der Corona-Krise? - Kristina Sommer (IU Internationale Hochschule, 2021)
– Camping is booming. This development, combined with the travel restrictions, led to an increase in the number of overnight stays at campsites in the summer of 2020. For example, there were more and more press reports of overcrowded campsites in the federal state of Mecklenburg-Western Pomerania. Camping tourism seems to be benefiting from the Corona crisis, while other tourism sectors are suffering from the effects of the crisis. But the demand for camping tourism in 2020 was very unevenly distributed and capacity was not effectively utilised. Alt-hough the summer season shifted and demand continued until September, campsites open all year round in particular suffered from the loss of the early and winter seasons. Losses could therefore not be compensated by a disproportionately positive summer season.
Keywords: 650; Camping; Campingtourismus; Campingplatz; Beherbergung; Caravaning